2011
DOI: 10.1148/radiol.11101176
|View full text |Cite
|
Sign up to set email alerts
|

Superior Labral Anteroposterior Tears: Accuracy and Interobserver Reliability of Multidetector CT Arthrography for Diagnosis

Abstract: Multidetector CT arthrography shows high accuracy and good interobserver reliability for diagnosis of SLAP lesions in spite of its limitations in specific classification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 26 publications
(48 reference statements)
0
18
0
Order By: Relevance
“…13,17 There is also evidence to suggest that computed tomography (CT) arthrography may also be used to distinguish between normal variants and SLAP lesions but with significantly decreased capability of staging of SLAP lesions compared with MRA. 18 Limitations of this technique include poor assessment of associated partial-thickness rotator cuff tears, reduced sensitivity to the detection of paralabral cysts, inability to assess bone marrow, and the necessity for radiation exposure.…”
Section: Imaging Techniquesmentioning
confidence: 99%
“…13,17 There is also evidence to suggest that computed tomography (CT) arthrography may also be used to distinguish between normal variants and SLAP lesions but with significantly decreased capability of staging of SLAP lesions compared with MRA. 18 Limitations of this technique include poor assessment of associated partial-thickness rotator cuff tears, reduced sensitivity to the detection of paralabral cysts, inability to assess bone marrow, and the necessity for radiation exposure.…”
Section: Imaging Techniquesmentioning
confidence: 99%
“…MDCT arthrography has been shown to be effective in accurately detecting SLAP lesions and distinguishing between normal variants affecting the anterosuperior labrum and labral-bicipital complex. [57][58][59] Chondral defects in various joints are well assessed using MDCT arthrography with accuracy in some cases superior to that of direct MR arthrography [60][61][62][63]. Sensitivity for abnormalities that do not involve the chondral surface, however, is limited when compared with conventional MR imaging.…”
Section: Miscellaneousmentioning
confidence: 99%
“…Waldt et al (10) reported that multidetector computed tomographic (CT) arthrography showed similar diagnostic performance. One reason specificity is lower than sensitivity is that many individuals have a sublabral recess, which might be mistaken for a labral tear (15). Hence, we hypothesized that diagnostic performance would increase if tension on the labral-bicipital complex from the glenoid insertion was applied during imaging.…”
Section: Patientsmentioning
confidence: 99%
“…head of the biceps tendon during CT arthrography and that SLAP lesions might thus be more easily differentiated from the normal sublabral recesses, which has been a clinical problem (15).…”
Section: Detection Of Slap Lesionsmentioning
confidence: 99%